Efficiency Of Combination Drugs In The Treatment Of Reversible Pulpitis - Jambilov Ravshanbek Sotvoldievich (Zien Journals, 2024)
The article presents a clinical evaluation of the effectiveness of combination drugs containing topical corticosteroids in the treatment of recurrent forms of pulpitis. It was found that when using a combination drug containing an antibiotic and a local corticosteroid, a pronounced analgesic effect occurs, which occurs in 22% of cases in the first hours after using the drug, in 66.7% - within 24 hours. The use of a paste containing an antibiotic and a local corticosteroid is justified for maintaining the viability of the pulp due to its pronounced anti-inflammatory and antimicrobial effect and preservation throughout the rehabilitation period in 77.8% of patients.
Keywords: reversible pulpitis; treatment; recurrent